Frequency of Metabolic Risk Factors and Association with Demographic Characteristics in Patients with Non-alcoholic Fatty Liver Disease : Metabolic Risk Factors and Demographic Characteristics with NAFLD - Gul, Tajwar; Kidwai, Saera Suhail; Kamran, Muhammad; Basit, Hafiz Abdul; Ishfaq, Afsheen; Umar, Mehrunisa (Pakistan Journal of Health Sciences, 2026)
Non-alcoholic fatty liver disease is a rapidly growing public health concern worldwide and is closely associated with metabolic and cardiovascular risk factors. Objectives: To determine the frequency and demographic associations of metabolic and cardiovascular risk factors among patients with NAFLD. Methods: This analytical cross-sectional study was conducted at the Department of Medicine, Fazaia Ruth Pfau Medical College, Base Faisal, Karachi, from June 2025 to December 2025. A total of 121 patients with NAFLD were enrolled through consecutive sampling. Diagnosis was based on elevated alanine aminotransferase levels and ultrasonographic evidence of fatty liver. Patients with significant alcohol intake, viral hepatitis, or other chronic liver diseases were excluded. Results: The mean age of the patients was 37.18±10.30 years, with a mean BMI of 27.27±4.27 kg/m², and a predominance of males (80.2%). Diabetes mellitus was present in 16.5% of patients, hypertension in 15.7%, and ischemic heart disease in 5.8%. Dyslipidemia was frequently observed, with hypertriglyceridemia in 47.1% and hypercholesterolemia in 27.3%, while obesity was identified in 31.4% of cases. A significant association was observed between age greater than 40 years and the presence of diabetes, hypertension, and ischemic heart disease (p<0.001). Conclusion: NAFLD is strongly associated with metabolic risk factors, particularly dyslipidemia and obesity, with a significant clustering of cardiovascular comorbidities in older individuals.